Quantification of Nimesulide in Human Plasma by High-Performance Liquid Chromatography with Ultraviolet Detector (HPLC-UV): Application to Pharmacokinetic Studies in 28 Healthy Korean Subjects - Kim, Mi-Sun; Park, Yoo-Sin; Kim, Shin-Hee; Kim, Sang-Yeon; Lee, Min-Ho; Kim, Youn-Hee; Kim, Do-Wan; Yang, Seok-Chul; Kang, Ju-Seop (Journal of chromatographic science, 2012)
Nimesulide is a selective COX-2 inhibitor that is as effective as the classical non-acidic nonsteroidal anti-inflammatory drugs in the relief of various pain and inflammatory conditions, but is better tolerated with lower incidences of adverse effects than other drugs. After oral dose of 100 mg nimesulide to western subjects, a mean maximal concentration (Cmax) of 2.86 ∼ 6.5 µg/mL was reached at 1.22 ∼ 2.75 h and mean t1/2β of 1.8 ∼ 4.74 h. This study developed a robust method for quantification of nimesulide for the pharmacokinetics and suitability of its dosage in Korea and compared its suitability with other racial populations. Nimesulide and internal standard were extracted from acidified samples with methyl tert-butyl ether and analyzed by high-performance liquid chromatography with ultraviolet detection (HPLC-UV). The 28 healthy volunteers took 2 tablets of 100 mg nimesulide and blood concentrations were analyzed during the 24 h post dose. Several pharmacokinetic parameters were represented: AUC0-infinity = 113.0 mg-h/mL, Cmax = 12.06 mg/mL, time for maximal concentrations (Tmax) = 3.19 h and t1/2β = 4.51 h. These were different from those of western populations as follows: AUC was 14.5% and Cmax was 28% that of of Korean subjects and Tmax and t1/2β were also different. The validated HPLC-UV method was successfully applied for the pharmacokinetic studies of nimesulide in Korean subjects. Because the pharmacokinetics of nimesulide were different from western populations, its dosage regimen needs to be adjusted for Koreans.